2021
DOI: 10.1111/geb.13407
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance frequency, intensity and forest structure modulate cyclone‐induced changes in mangrove forest canopy cover

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 76 publications
2
21
0
Order By: Relevance
“…We found that damages caused to forest vegetation by TCs based on NDVI changes were negligible for winds <50 m/s, i.e., for category 1-2 TCs (SSHWS). This is consistent with recent conclusions reached by Peereman et al [13] on global mangroves. Above this breakpoint, reduction in NDVI increased linearly with increasing wind speed which likely resulted from increasing major damages to vegetation, including branch breaking, tree uprooting, and bole snapping.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that damages caused to forest vegetation by TCs based on NDVI changes were negligible for winds <50 m/s, i.e., for category 1-2 TCs (SSHWS). This is consistent with recent conclusions reached by Peereman et al [13] on global mangroves. Above this breakpoint, reduction in NDVI increased linearly with increasing wind speed which likely resulted from increasing major damages to vegetation, including branch breaking, tree uprooting, and bole snapping.…”
Section: Discussionsupporting
confidence: 94%
“…The TC regime could also play a role in the effects of these disturbances on forests. Forests that have been historically exposed to frequent intense TCs are likely to be acclimated or adapted to these disturbances and thus could be more resistant to TCs than forests that have been historically rarely exposed to these disturbances [13]. Different levels of resistance of different forest types also probably explain the large variation in observed damages for a given maximum sustained wind speed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of cyclone impacts on mangrove forests is not only dependent on cyclone‐induced storm surge and high velocity winds, but also on factors such as structural composition and heterogeneity of the vegetation, canopy cover, canopy height, species traits, and their spatial arrangement in the mangrove forest (Krauss & Osland, 2020; Peereman et al., 2021). The current status of mangrove forests is defined by a legacy of past tropical cyclones and recovery regime (Awty‐Carroll et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Individual hurricane disturbances represent distinct events that drastically influence successional trajectories of a forest by shaping forest structure (e.g., maximum tree heights and biomass), tree population dynamics (e.g., recruitment and mortality rates), and tree growth, over decades and centuries (Bellingham et al, 1995; Brokaw & Grear, 1991; Lin et al, 2020; McLaren et al, 2019; Zimmerman et al, 1994). For example, tropical forest structure and canopy architecture are shaped by cyclone disturbance frequency to varying degrees (de Gouvenain & Silander Jr., 2003; Ibanez et al, 2019; Peereman et al, 2022). Hurricane‐induced compositional changes can lead to varying successional trajectories of forests, altering species composition, and relative abundances of forest taxa in novel and ecologically important ways, especially when combined with other disturbances (Vandermeer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%